Serum high sensitivity C reactive protein and lipid profile in obese students - Trimbake, Sangeeta B.; Pratinidhi, Shilpa A.; Majithia, Yash K. (International Journal of Research in Medical Sciences, 2019)
Background: The prevalence of overweight and obesity is progressively increasing in younger and adult population in India. It is a medical problem that increases risk of other diseases and health problems, such as heart disease, diabetes, high blood pressure and certain cancers. One of the causes of dyslipidaemia is obesity. High sensitivity C-Reactive Protein (hs-CRP), is a marker of systemic inflammation and a predictor of type 2 diabetes and cardiovascular disease. Hence it is important to check the relationship of hs-CRP with lipid profiles in obese and non-obese students. Methods: A case control observational study was carried out in 60 students. They were divided in to two groups obese and non-obese based on the BMI ranges. Serum lipid levels, hs-CRP and BMI was estimated in both groups to find out correlation of hs-CRP with lipid profile and BMI. Results: There was a significant rise in serum Total Cholesterol, LDL-C, Triacylglycerol and a significant fall in HDL-C in obese group as compared to non-obese group. Serum hs-CRP and BMI was significantly increased in obese students as compared to non-obese students. There was statistically significant positive correlation found between hs-CRP and total cholesterol, LDL-C, Triacylglycerol in obese students. Conclusions: Significant correlation was found between hs-CRP and lipid profile except HDL-C. Serum hs-CRP levels may decrease by treatment of dyslipidaemia. This would minimize the incidence of atherosclerosis and hence decrease the risk for development of coronary artery disease. Hence, improving the quality of life.